Eugene Tyler Chamberlain collection relating to French orphans of World War I - Chamberlain, Eugene Tyler, 1856-1929.
Files on French families and orphans of World War I aided by Chamberlain and other philanthropic Americans. Chiefly correspondence concerning rehabilitation of the families and the education and placement of the children in productive employment. Files also contain photographs and memoranda providing family background.
Philanthrophist.
Collection material in French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Orphans -- France; World War, 1914-1918 -- Children -- France; World War, 1914-1918 -- Civilian relief -- France; World War, 1914-1918 -- France; Philanthropists